Impacto de la oficina virtual en el campo secretarial en la cooperativa de ahorro y crédito oscus ltda. ciudad Latacunga - Tandalla Arequipa, Blanca del Pilar (2015)
This research was done on the saving and Credit Oscus Ltda. branch Latacunga, located in the Matriz down town General Maldonado Avenue 5-56 and Quito, is a prestigious institution that applies human and institutional values at the moment that providing its service, its main objectives is to improve the quality of life of people through the financial services that give, so try to carryout the needs of users who are increasingly demanding in today's world….